High incidence of gynecologic sarcomas in Israel—A comparison to European and American reports: Gynecologic Sarcoma in Israel. (December 2021) - Brudner, Yana; Salman, Lina; Haran, Gabi; Blecher, Anna; Hallak, Mordechai; Bruchim, Ilan
Abstract: Objective: Gynecologic Sarcomas are rare, aggressive tumors. The aim of this study was to explore the incidence and outcomes of gynecologic sarcomas in a large national data registry and to compare them with reports from other countries. Study Design: Records of gynecologic sarcomas diagnosed in Israel (1980–2014) were extracted from the National Cancer Registry and classified according to International Classification of Diseases for Oncology-3 and characterized according to anatomical site, morphology and demographics. Age-standardized incidence rates and 1, 3, 5 and 10-year relative survival rates were calculated for 3 time periods (1980–1994, 1995–2001 and 2005–2014) according to patient age, stage and years of diagnosis. Results: During 1980–2014, 1271 new gynecologic sarcomas were diagnosed in Israel, with incidence slightly increasing in 1980–2004, to an age-standardized incidence rate of 13 per million women. The most common histologic diagnosis was leiomyosarcoma (48%) and the most common anatomical site was the uterus (89%). The age-standardized incidence rate for uterine sarcoma is higher in Israel (10.55 per million) than in England (7.4 per million) and Germany (5.8 per million) respectively. The 5-year overall survival was significantly poorer in patients >70-years, as compared to younger patients ( p <0.001) and in those with leiomyosarcoma compared to endometrial stromal sarcoma ( p <0.001). The survival rate of patients with leiomyosarcoma in Israel are comparable to survival rates reported by other studies, although substantially lower regarding endometrial stromal sarcoma. Conclusions: Uterine leiomyosarcoma was the most common gynecologic sarcoma found in the Israeli, European and American registries. Older patients and those with leiomyosarcoma have the worst prognoses. Histological and anatomical variations in Israel are comparable with global statistics, but the incidence in Israel seems higher than in Europe.